Jedność i nierozerwalność małżeństwa w pismach łacińskich ojców Kościoła z II i III wieku - Dzierżon, Ginter (Ius Matrimoniale, 2015)
The author of the presented article carried out an analysis of the writings of Early Christian Latin writers of 2nd and 3rd centuries concerning the unity and indissolubility of marriage. He pointed out that all of them stood for the unity of marriage (Tertullian, Marcus Minucius Felix, Saint Cyprian, Novatian). Some interpretative controversies arise among patrologists around the texts of Tertullian and Lactantius concerning the indissolubility of marriage. The author proved, mainly on the basis of the views of Crouzel, that these texts should be interpreted primarily in the context of conditions in which they were written. They should not be perceived as consent for a new marriage in the case of adultery.